The role of clinical evidence in emergent therapies: an empirical study on femoropopliteal stent-angioplasty in Europe - Bourdon, Elmar; Schüller, Katharina; Diehl, Steffen J. (Journal of evaluation in clinical practice, 2015)
Rationale, aims and objective: A delayed availability of clinical evidence in rapidly emerging therapies is considered a major problem. In this study, we examined whether evidence from clinical studies has influenced the therapy of a major disease in industrial countries, peripheral arterial disease (PAD), using novel femoropopliteal stent-angioplasty. Method: This analysis of retrospective time series data uses multivariate linear regression to investigate associations between published clinical evidence on femoropopliteal stent-angioplasty from Q3/2004 to Q4/2010 and the demand for femoropopliteal stents in Germany, France, Italy and the UK between Q1/2005 and Q4/2010, controlling for the prevalence of PAD risk factors, cardiovascular drug demand, reimbursement of health care providers for stent implantation, stent selling prices of manufacturers and economic indicators. Results: We did not observe any association of published clinical evidence with femoropopliteal stent demand in Germany, France, Italy and the UK, while we observed such associations for varying control variables at different time lags respectively. Conclusion: We observed no association between published clinical evidence of femoropopliteal stent-angioplasty and its use in any of the four countries. The country-specific context and practice-related variables at a centre and individual doctor level may have limited the role of published clinical evidence in emerging femoropopliteal stent-angioplasty. More research is needed at this context, centre and individual level.
Gesehen am 06.09.2017